2011
DOI: 10.1017/s000712341100024x
|View full text |Cite
|
Sign up to set email alerts
|

Scandal Fatigue? Scandal Elections and Satisfaction with Democracy in Western Europe, 1977–2007

Abstract: Elections involving a major scandal were unusual in the late 1970s, but today nearly half are so affected. Multilevel analyses of Eurobarometer data reveal that scandal elections once had negative net effects on satisfaction with democracy. However, as scandals have become more common, the negative effect has withered away. This ‘scandal fatigue’ process appears driven by changes in scandal material, rather than by changes in citizens’ reactions to a given type of material. Scandals involving several politicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 33 publications
2
63
1
Order By: Relevance
“…Key's reputation, as a politician who could be trusted and the leader of a competent government, came under question from two directions: first, the so-called 'dirty politics' affair; and second, political competition from an unlikely source, internet entrepreneur Kim Dotcom. Politicians are often vulnerable to sudden 'scandals', particularly during election campaigns, as a growing literature demonstrates (for example, Hirano and Synder 2012;Kumlin and Esaiasson 2012). Given how close National came to being able to form a single-party majority government in 2014, it is possible that the marginal effects of these challenges could have made a difference.…”
Section: Leadership and Competencementioning
confidence: 99%
“…Key's reputation, as a politician who could be trusted and the leader of a competent government, came under question from two directions: first, the so-called 'dirty politics' affair; and second, political competition from an unlikely source, internet entrepreneur Kim Dotcom. Politicians are often vulnerable to sudden 'scandals', particularly during election campaigns, as a growing literature demonstrates (for example, Hirano and Synder 2012;Kumlin and Esaiasson 2012). Given how close National came to being able to form a single-party majority government in 2014, it is possible that the marginal effects of these challenges could have made a difference.…”
Section: Leadership and Competencementioning
confidence: 99%
“…This lack of impact on satisfaction with democracy occurs today due to citizens' weariness. The higher the number of scandals experienced by the public, the greater their capacity to weigh their impact and therefore, the fewer the consequences arising from them (Kumlin and Esaiasson, 2012). In contrast, other authors have found different evidence and argue that the perception of corruption is negatively related to satisfaction with democracy.…”
Section: Participation and Political Culturementioning
confidence: 99%
“…Despite cultural differences, we expect that the basic mechanisms operate and remain the same for established democracies and post-transitional countries. Nevertheless, since most studies pertaining to political scandals have been conducted in English-speaking populations (Berinsky et al, 2010;Puglisi & Snyder, 2011;Vivyan, Wagner, & Tarlov, 2012) and Western democracies (Cepernich, 2008;Kumlin & Esaiasson, 2012;Maier, 2011), research in other contexts such as this one must continue to help better understand scandals across various political conditions.…”
Section: Limitations and Suggestions For Further Workmentioning
confidence: 99%
“…Given the potential for political scandals to destabilize the status quo, the topic of political scandals has received attention from numerous scholars in psychology, political sciences, journalism or law. Regardless of the scientific disciplines, most studies focus on one type of scandal, mainly corruption or sexual (Cepernich, 2008;Maier, 2011;Puglisi & Snyder, 2011;Wiid, Pitt, & Engstrom, 2011) and on male politicians in established democracies (Berinsky et al, 2010;Kumlin & Esaiasson, 2012;Maier, 2011;Vivyan, Wagner, & Tarlov, 2012). In this research, we focus on how reactions to politicians involved in scandals might differ as a function of the type of scandal and the gender of the politician while also considering factors that may be responsible for influencing electability.…”
Section: Introductionmentioning
confidence: 99%